Dynamic Arterial Elastance During Experimental Endotoxic Septic Shock: A Potential Marker of Cardiovascular Efficiency - Monge Garcia, Manuel Ignacio; Guijo González, Pedro; Saludes Orduña, Paula; Gracia Romero, Manuel; Gil Cano, Anselmo; Messina, Antonio; Rhodes, Andrew; Cecconi, Maurizio (Frontiers in Physiology, 2020)
Dynamic arterial elastance (Eadyn), the ratio between pulse pressure variation (PPV) and stroke volume variation (SVV), has been suggested as a dynamic parameter relating pressure and flow. We aimed to determine the effects of endotoxic septic shock and hemodynamic resuscitation on Eadyn in an experimental study in 18 New Zealand rabbits. Animals received placebo (SHAM, n=6) or intravenous lipopolysaccharide (E. Coli 055:B5, 1 mg·kg-1) with or without (EDX-R, n=6; EDX, n=6) hemodynamic resuscitation (fluid bolus of 20 ml·kg-1 and norepinephrine for restoring mean arterial pressure). Continuous arterial pressure and aortic blood flow measurements were obtained simultaneously. Cardiovascular efficiency was evaluated by the oscillatory power fraction (%Osc: oscillatory work / left ventricular (LV) total work) and the energy efficiency ratio (EER = LV total work/cardiac output). Eadyn increased in septic animals (from 0.73 to 1.70; p=0.012) and dropped after hemodynamic resuscitation. Eadyn was related with the %Osc and EER [estimates: -0.101 (-0.137 – -0.064) and -9.494 (-11.964 – -7.024); p<0.001, respectively]. So, the higher the Eadyn, the better the cardiovascular efficiency (lower %Osc and EER). Sepsis resulted in a reduced %Osc and EER, reflecting a better cardiovascular efficiency that was tracked by Eadyn. Eadyn could be a potential index of cardiovascular efficiency during septic shock.